PEMBENTUKAN WADAH SUBAK- GDE DI DAERAH IRIGASI KEDEWATAN KABUPATEN GIANYAR - I WAYAN WINDIA; KETUT SUAMBA (Buletin Udayana Mengabdi, 2007)
ABSTRACT Basically now, the water available is scarcer. Meanwhile, the population growth that occurs so fast, which is followed by increasing of public prosperity and development of other sectors beyond agricultural sector, causing the increase in water need, both quantitatively and qualitatively. That is why; the water need is very competitive among sectors. Generally, in the field the water need for farmers often to be defeated by the other sectors (especially by the tourism sector).The same situations is feeled by farmers in subaks, who getting water from the Kedewatan Dam, in Sub Regency of Ubud, Regency of Gianyar. Some international hotels in the head of the dam freely take water from the river, and moreover in the tail of the dam, rafting activities and the Drinking Water of The Government of Denpasar Company often borrowing water from the dam. Therefore, the water available for the subaks is disturbed. According to those conditions, is very important to motivate the all head of subaks those getting water from the Kedewatan Dam to organize themselves in the institution of subak coordination body (subak-gde). Anyhow, that organization is important to strengthen the subak position in their negotiation activities with the outsider. In these community service activities, basically the all of subak is very agree to construct the subak coordination body (subak-gde).